2015
DOI: 10.1016/j.celrep.2015.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Sequestration of miR165/166 by Arabidopsis Argonaute10 Promotes Shoot Apical Meristem Maintenance

Abstract: Arabidopsis Argonaute10 (AGO10) specifically sequesters miR165 and miR166 and antagonizes their activity, thus regulating shoot apical meristem (SAM) development. However, where and when this sequestration acts is currently unclear. We show here that AGO10 represses miR165/166 activity in the embryo proper during early embryogenesis, through the apical and central regions of mature embryos, and eventually in the entire adaxial domain and vasculature of the cotyledons and leaf primordia. These locations are ess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 22 publications
2
72
0
1
Order By: Relevance
“…AtAGO10 is closest to AtAGO1, and it regulates shoot apical meristems by sequestering miR165/166 [16][17][18]. The miR165/166 family is produced from nine Arabidopsis loci and targets class III homeodomain-leucine zipper (HD-ZIP III) transcription factors.…”
Section: Features and Functions Of Plant Ago Proteinsmentioning
confidence: 99%
“…AtAGO10 is closest to AtAGO1, and it regulates shoot apical meristems by sequestering miR165/166 [16][17][18]. The miR165/166 family is produced from nine Arabidopsis loci and targets class III homeodomain-leucine zipper (HD-ZIP III) transcription factors.…”
Section: Features and Functions Of Plant Ago Proteinsmentioning
confidence: 99%
“…As mentioned above, AGO10 specifically sequesters miR165/166 and abrogates their activities . A recent study showed that AGO10 quenches the activity of miR165/166 that moves into AGO10-expressing zone, thus releasing the expression of HD-ZIP III family genes to regulate meristem development (Zhou et al, 2015). In addition to sequestering miR165/166, AGO10 may regulate meristem development through mediating the translational inhibition of multiple miRNA target genes (Brodersen et al, 2008;Mallory et al, 2009) and act partly through miR172 to promote floral determinacy (Ji et al, 2011).…”
Section: Ago1/5/10 Cladementioning
confidence: 99%
“…Arabidopsis AGO7 (also known as ZIP) specifically binds miR390 (Montgomery et al, 2008), which targets TAS3 transcripts (Bohmert et al, 1998;Morel et al, 2002;Vaucheret et al, 2004;Baumberger and Baulcombe, 2005;Qi et al, 2005;Zhang et al, 2006) ta-siRNAs vsiRNAs OsAGO1a Os02g45070 miRNAs Plant development, antiviral defense Os04g47870 miRNAs Plant development, antiviral defense (Wu et al, , 2015 (Takeda et al, 2008;Tucker et al, 2012;Brosseau and Moffett, 2015) vsiRNAs OsAGO5c Os03g58600 phasiRNAs Germ cell division (Nonomura et al, 2007;Komiya et al, 2014) AtAGO10 AT5G43810 miR165/166 SAM development, antiviral defense (Moussian et al, 1998;Lynn et al, 1999;Liu et al, 2009;Ji et al, 2011;Zhu et al, 2011;Garcia-Ruiz et al, 2015;Zhou et al, 2015) miR172 vsiRNAs (Harvey et al, 2011;Jaubert et al, 2011;Wang et al, 2011b;Zhang et al, 2011;Wei et al, 2012) vsiRNAs miR393* AtAGO3 AT1G31290 n.d. n.d. AtAGO7 AT1G69440 miR390 ta-siRNA biogenesis, phase transition, antiviral defense (Hunter et al, 2003;Adenot et al, 2006;Montgomery et al, 2008;Qu et al, 2008) OsAGO7 Os03g33650 miR390 ta-siRNA biogenesis, SAM development (Nagasaki et al, 2007) ZmAGO7 GRMZM5G892991 miR390 ta-siRNA biogenesis, leaf development (Douglas et al, 2010) AtAGO4 AT2G27040 hc-siRNAs DNA methylation, antibacterial immunity, defense against DNA viruses (Zilberman et al, 2003;Li et al, 2006;Pontes et al, 2006;…”
Section: Ago2/3/7 Cladementioning
confidence: 99%
“…AGO10 sequesters these miRNA preferentially in AGO10 expressing niches, thus preventing these miRNA from getting into AGO1. This helps in the proper expression of miR165/miR166 target genes and mediate SAM development (Zhou et al, 2015;Liu et al, 2008;Zhu et al, 2011). It has been established that sequestration of miR165/166 into AGO10 depends on its duplex structure (Zhu et al, 2011).…”
Section: Loading Of Mirna Into Ago and Silencingmentioning
confidence: 99%